Pengembangan Sistem Penggajian Pada Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Kota Metro - Anie Rose Irawati; Machudor Yusman; Lenny Tiarma Sinaga (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
The development of technology which are grow faster requires any person or institutions to do their job quickly. Payroll system is one of many important things at any institution. To calculate employeeâ€™s salary accurately and quickly a computerized system is need. Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) in Metro City is an institution that is responsible to the community services. The process of payroll system on this institution has been done using computer in semi manual way. Therefore this institution needs a computerized system that could calculate employee salary automatically. On this research was made a payroll system that integrated with crystal report of finger print attendance system. Payroll system can convert data from crystal report of finger print attendance systems for calculate the salary of employee. In addition, the system can cut withholding tax, cut delay or go home before time home, and presenting more detail attendance and salaries recapitulation report of employees. This research used visual basic 6.0 as programming language, MySQL as database, andÂ crystal report to perform reports. The method of development system that used in this research is waterfall method. The result of Black Box Testing showed that payroll system has been successfully built according to user requirement.